The obstacle is the way : the ancient art of turning adversity to advantage / Ryan Holiday. - Holiday, Ryan (Profile Books, 2015)
We give up too easily. With a simple change of attitude, what seem like insurmountable obstacles become once-in-a-lifetime opportunities. Ryan Holiday, who dropped out of college at nineteen to serve as an apprentice to bestselling 'modern Machiavelli' Robert Greene and is now a media consultant for billion-dollar brands, draws on the philosophy of the Stoics to show you how in every situation, that what blocks our path actually opens one that is new and better.